INTERNALISASI NILAI-NILAI KEISLAMAN MODERAT PADA MASYARAKAT DUSUN NGERING, CERME, GRESIK - kafiyah, Iis; Ali Ahmad Yenuri (Journal Multicultural of Islamic Education, 2024)
This study explores how moderate Islamic education values are instilled in the daily life of the community in Dusun Ngering, Cerme Subdistrict, Gresik Regency. The research focuses on the strategic roles of two major Islamic organization Nahdlatul Ulama (NU) and Muhammadiyah (MD) in facilitating this internalization process. Employing a qualitative approach with a case study desighn, data were collected through direct observation, in depth interviews with local religious figures and community leaders, as well as document analysis. The findings reveal that core values of Islamic moderation such as a balance (tawassuth), justice (i’tidal), tolerance (tasamuh), deliberation (syura), and patriotism (muwathonah) are effectively integrated through religious activities, formal and informal education, and the moral example set by religious activities, formal and informal education, and the moral example set by religious leaders. NU and MD actively guide the community toward an inclusive and peaceful practice of Islam. Nevertheless, the process faces challenges, particularly from digital media influences and cultural shifts impacting younger generations. Overall, the internalization of these values contributes significantly to shaping a religious, open-minded, and socially harmonious community.